الخطاء اللغوي: التدخل في التعبير الشفوي لدى الطلاب بمركز اللغة العربية في المعهد القادري الإسلامي جمبر - M.Hari Zakiyudin; Inayatul Mukarromah; Nur Hasan (FASHOHAH, 2022)
Arabic learners often encounter obstacles in the form of interference from their mother tongue or the first language they master. This is one of the consequences of using the mother tongue too often in daily conversation and is included as one of the language errors. This study aims to (1) determine the process of language interference in Arabic against students in the Arabic language learning center area at the Al-Qodiri Islamic Boarding School Jember, (2) find out the types of language interference. This research uses descriptive qualitative research to get the results the researcher wants. The results of this study indicate that there are 3 types of language interference, namely: arrangement interference, morphological interference (prefix-infic-suffix) and syntactic interference (grammatical).